2016
DOI: 10.1002/art.39784
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Secretory Activity of Neutrophils With Genotype in Patients With Familial Mediterranean Fever

Abstract: The FMF phenotype is known to be more severe in patients carrying the p.M694V mutation. This report describes 2 molecules secreted by unconventional secretory pathways, S100A12 and IL-18, whose concentrations correlated with clinical disease activity and genotype in patients with FMF. In this clinically and genetically heterogeneous disease, management of these surrogate markers might help to improve patient care and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 53 publications
5
35
0
1
Order By: Relevance
“…Gohar et al demonstrated that in vitro , unstimulated neutrophils from M694V positive patients spontaneously secreted more S100A12, IL-18, and caspase-1 compared to neutrophils from healthy controls (61). In another study, it has recently been shown that FMF attack is characterized by release of neutrophil extracellular traps (NET) including active IL-1β (60).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…Gohar et al demonstrated that in vitro , unstimulated neutrophils from M694V positive patients spontaneously secreted more S100A12, IL-18, and caspase-1 compared to neutrophils from healthy controls (61). In another study, it has recently been shown that FMF attack is characterized by release of neutrophil extracellular traps (NET) including active IL-1β (60).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…Furthermore, we identified that neutrophils actively contribute to skin inflammation via production of IL‐1β and IL‐18 in lesional SchS skin. In line with this finding, neutrophils secrete high amounts of IL‐1β and IL‐18, and high serum IL‐18 levels were shown to correlate with clinical disease activity in the prototype autoinflammatory disease, familial Mediterranean fever . Neutrophils are also known to express pattern recognition receptors and to signal via the NLRP3 inflammasome .…”
mentioning
confidence: 64%
“…In line with this finding, neutrophils secrete high amounts of IL-1b and IL-18, and high serum IL-18 levels were shown to correlate with clinical disease activity in the prototype autoinflammatory disease, familial Mediterranean fever. 8 Neutrophils are also known to express pattern recognition receptors and to signal via the NLRP3 inflammasome. 9 In SchS, dysfunctional inflammasome components were reported, and the neutrophil NLRP3 inflammasome may play a critical role in the caspase-1-dependent secretion of IL-1b in this disease.…”
mentioning
confidence: 99%
“…In 2 aktuellen Studien waren SAA und CRP bei Patienten mit FMF im Hinblick auf die oben aufgeführten Fragen gleichwertig [29,51]. In aktuellen Studien waren die S100-Moleküle aus der Gruppe der Calgranuline den beiden klassischen Biomarkern hinsichtlich der Sensitivität der Detektion von Inflammation bei Patienten mit FMF überlegen [52][53][54]. Eine Analyse der Daten aus dem deutschen Register für autoinflammatorische Erkrankungen (AID-Net-Register) erbrachte, dass bei symptomatischen pädiatrischen und jugendlichen FMF-Patienten eine Kombination aus Biomarkern mit Einschluss der S100-Moleküle den Vorhersagewert für eine erforderliche Intensivierung der Therapie deutlich erhöht [29].…”
Section: Prinzipunclassified